Empowering frail older adults: multicomponent elastic-band exercises and BCAA supplementation unleash physical health and preserve haematological biomarkers - Caldo-Silva, Adriana; Furtado, Guilherme E.; Chupel, Matheus Uba; Letieri, Rubens Vinícius; Neves, Rafael Santos; Direto, Fábio; Barros, Marcelo P.; Bachi, André L. L.; Matheu, Ander; Martins, Faber; Massart, Alain; Teixeira, Ana Maria (Frontiers in Sports and Active Living, 2023)
The effectiveness of Branched Chain Amino Acids (BCAAs) supplementation on enhancing exercise performance in both young and older adults remains a topic of debate. Recent research suggests that BCAAs combined with regular exercise might have an impact on human erythropoiesis, blood dynamics, and iron homeostasis. Given the increasing longevity of the global population, it is crucial to investigate the potential benefits of BCAA supplementation and regular exercise as nonpharmacological interventions for improving the overall health of frail older adults. To assess the influence of a 40-week multicomponent exercise intervention (MEP) combined BCCA supplementation on the haematological indicators of frail older adults (83-93 years old) residing in nursing homes. A prospective, naturalistic, controlled clinical trial employing an interventionwashout-intervention was conducted for this purpose. The study included four experimental groups: MEP plus BCAA supplementation (MEP+BCAA, n = 8), MEP only (n = 7), BCAA supplementation only (n = 7), and control group non exercising (CG, n = 13). Fried's physical frailty (PF) protocol was employed to stratify the participants. Additionally, the assessment included the evaluation of nutritional status, comorbidities, and anthropometric measurements. Among the several haematological markers examined, only mean cellular Haemoglobin Concentration (MCH) [F = 4.09; p< 0.03] and Mean Cell haemoglobin Concentration (MCHC) [F= 10, 323; p<0,0001] showed significant effects of time group. Our findings demonstrate that a long-term intervention with BCAA plus MEP did not lead to significant alterations in the haematological profile. An 8-week withdrawal from interventions did not affect the frailty status in the MEP and MEP+BCAA groups, whereas the control group exhibited an increase in PF status. The findings, demonstrating the potential proimmune effect and maintenance of MCH and MCHC levels, highlight the relevance of incorporating exercise and nutritional strategies to promote healthy aging. This study contributes to the achievement of the United Nations Sustainable Development Goals 3 (good health and well-being) and 10 (reduced Inequalities) for all.